2015
DOI: 10.3109/08830185.2015.1018416
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary Lymphoid Tissue in the Tumor Microenvironment: From Its Occurrence to Immunotherapeutic Implications

Abstract: Recruitment of immune and inflammatory cells in the microenvironment of solid tumors is highly heterogeneous and follows patterns, varying according to the organ of origin and stage of disease, with critical roles in the process of cancer onset and progression. While adaptive cells are endowed with anti-tumor activities, inflammatory components of the immune infiltrate orchestrate an immunosuppressive microenvironment that reveals ambivalent functions of the immune contexture in the tumor milieu. The balance b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 68 publications
0
24
0
Order By: Relevance
“…The pattern of tumour-infiltrating lymphocyte (TIL) distribution identified dispersed lymphocytes or the presence of discrete lymphoid aggregates with features of ELSs mainly at the edges of large tumour nodules (Supplementary Figure S4A ). ELSs are lymphoid structures that develop in nonlymphoid tissue and have an organisation similar to that of lymph nodes [ 22 , 23 ]. In our samples, they showed discrete T (CD3 + ) and B (CD20 + ) cell areas, the first containing a CD21-positive follicular dendritic cell (FDC) network and the latter VEGFR2-positive endothelial venules, thus fulfilling the criteria for organised lymphoid structures (Supplementary Figure S4 ) [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…The pattern of tumour-infiltrating lymphocyte (TIL) distribution identified dispersed lymphocytes or the presence of discrete lymphoid aggregates with features of ELSs mainly at the edges of large tumour nodules (Supplementary Figure S4A ). ELSs are lymphoid structures that develop in nonlymphoid tissue and have an organisation similar to that of lymph nodes [ 22 , 23 ]. In our samples, they showed discrete T (CD3 + ) and B (CD20 + ) cell areas, the first containing a CD21-positive follicular dendritic cell (FDC) network and the latter VEGFR2-positive endothelial venules, thus fulfilling the criteria for organised lymphoid structures (Supplementary Figure S4 ) [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Stromal spindle cells are major components of tissue inflammation or tertiary lymphoid structures within the microenvironment. [ 16 18 ] Recent studies showed that stromal spindle cells and fibroblasts actively regulate immune cells in the inflammatory process and are involved in immune escape of cancers. [ 16 , 34 , 35 ] In addition, fibroblasts and stromal spindle cells, or cancer-associated fibroblasts (CAFs), are major components of the tissue matrix.…”
Section: Discussionmentioning
confidence: 99%
“…The secondarily induced NOVA1 suppression in spindle cells and T cells may result in abnormal tissue matrix function and immune regulation. In fact, stromal spindle cells actively regulate immune cells, as they are major components of tissue inflammation or tertiary lymphoid structures within the microenvironment [1][2][3]. Therefore, blocked NOVA1 function in these microenvironment cells may be related to immune escape of aggressive cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor growth involves coevolutionary processes among tumor cells, extracellular matrix, vasculatures, and immune cells [1]. Cancer-associated inflammation or tertiary lymphoid structures made by ectopically accumulated immune lymphoid cells and matrix components are formed within the tumor microenvironment as an immune reaction in response to stimuli of tumor growth [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation